2017
DOI: 10.1021/acscatal.7b00366
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Core–Shell Catalyst with Nitride Nanoparticles as a Core: Well-Defined Titanium Copper Nitride Coated with an Atomic Pt Layer for the Oxygen Reduction Reaction

Abstract: A class of core-shell low-platinum catalyst, with well-dispersed inexpensive titanium copper nitride nanoparticles as cores and atomic platinum layers as shells exhibiting high activity and stability for the oxygen reduction reaction (ORR) is successfully developed. Using nitrided carbon nanotubes (NCNTs) as the support greatly improved the morphology and dispersion of the nitride nanoparticles, resulting in significant enhancement of the catalyst's performance. The optimized catalyst, Ti0.9Cu0.1N@Pt/NCNTs, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 50 publications
0
62
0
Order By: Relevance
“…In a previous study, imperfect Pt coverages on a non‐noble core material has led to fast and quantitative dissolution of the core revealing the need for material combinations that can withstand the harsh ORR conditions . Early transition metal carbides were reported to exhibit metallic conductivity, high corrosion resistance and are able to strongly bind to noble metals such as Pt anchoring it in place . Our own research revealed stabilization of tungsten carbide compared to bare tungsten, and we were able to identify the metal‐carbon bond enthalpy as stabilization criterion for various metal carbides .…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…In a previous study, imperfect Pt coverages on a non‐noble core material has led to fast and quantitative dissolution of the core revealing the need for material combinations that can withstand the harsh ORR conditions . Early transition metal carbides were reported to exhibit metallic conductivity, high corrosion resistance and are able to strongly bind to noble metals such as Pt anchoring it in place . Our own research revealed stabilization of tungsten carbide compared to bare tungsten, and we were able to identify the metal‐carbon bond enthalpy as stabilization criterion for various metal carbides .…”
Section: Resultsmentioning
confidence: 63%
“…While platinum (Pt) is the element with the highest specific activity towards the ORR, its scarcity is its major disadvantage . An interesting, yet not industrially established concept comprises the use of core‐shell structures with a cost‐efficient core material that supports a noble metal film with a thickness lying in the monolayer (ML) range . The main advantages of such a design over monometallic catalysts are enhanced SA, a drastic decrease in noble metal loading and significant cost benefits .…”
Section: Introductionmentioning
confidence: 99%
“…And after 10,000 potential cycles, the TiN@Pt and TiNiN@Pt catalysts only degraded by a negative shift of 17 and 10 mV in its half-wave potential, respectively, whereas Pt/C showed a degradation of more than 25 mV (E 1/2 ), demonstrating the long-term stability of the resulting TiNiN@Pt catalyst. Other bimetallic nitride cores covered by Pt shells, such as PdNiN, TiWN, and TiCuN, have also been reported to display enhanced catalytic activities and stabilities for ORR [547][548][549] and these developments open up broad feasibilities for the design and synthesis of various TMN nanoparticle-based core-shell structures for applications in electrocatalysis. However, many problems still exist for TMN core applications.…”
Section: Nitrides As Corementioning
confidence: 99%
“…Adzic and co-workers have fabricated various core-shell electrocatalysts with monolayer and ultrathin Pt shell via Cu under potential deposition (UPD) and pulse electrodeposition (PED). The core materials contain intermetallics (PtPb, PdPb, PdFe) [70], core-shell (Pd@PdAu) [71], alloy (AuNi) [72] and transition metal nitride (TiCuN) [73]. As shown in Figure 3, in an UPD process, they prepared core first, then dropped onto a flat glassy electrode to form a thin film.…”
Section: Core-shell Structures With Ultrathin Pt Shellmentioning
confidence: 99%